Inflammatory Response of Healthy Horses Subjected to Small Colon Enterotomy and Treated or Not With Heparin - Alonso, Juliana de M. [UNESP]; Schmidt, Elizabeth M.S. [UNESP]; Eckersall, Peter D.; Kjelgaard-Hansen, Mads; Alves, Ana Liz G. [UNESP]; Rodrigues, Celso A. [UNESP]; Watanabe, Marcos J. [UNESP]; Crescencio, Amanda P. [UNESP]; Hussni, Carlos A. [UNESP] (Elsevier, 2020)
The acute phase response is a response to injury and depends on the severity of the trauma. Heparin is routinely used for postsurgical treatment of horses to prevent abdominal adhesions; however, its effect on inflammation is unknown. This study aimed to assess systemic inflammatory response of horses subjected to small colon enterotomy and to evaluate heparin effects on postsurgical inflammation. Ten adult horses were subjected to small colon enterotomy and were assigned to a control or a treatment group. Both groups received prophylactic antibiotics and flunixin, and the treatment group received 150 IU/kg heparin subcutaneously after surgery and every 12 hours for five days. WBC counts, peritoneal fluid evaluation, determination of serum and peritoneal haptoglobin (Hp), and serum amyloid A (SAA) were performed before, 12 hours, and 1, 2, 4, 6, 10, and 14 days after enterotomy. Forty-eight hours after surgery, a significant increase in serum Hp was observed in the control group, and SAA concentrations increased significantly in the both groups between 24 hours, 48 hours, and 4 days after surgery. The SAA and serum Hp concentrations produced no significant differences between the groups. Peritoneal Hp increased significantly in the control group 4 days after surgery and was significantly higher in the control group than in the treated group 14 days after surgery. Serum Hp and SAA identified the acute phase response changes faster, however, were not able to identify differences between groups. Peritoneal Hp concentrations identified inflammatory differences between the groups 14 days after surgery; the difference suggests that heparin may act decreasing inflammation.
Keywords: Acute phase response; Haptoglobin; Horse; Inflammation serum amyloid A